SPR-spectroscopy of protein molecules adsorbed in microwave field - Berezhinsky, L.I.; Chegel', V.I.; Shirshov, Yu.M.; Dovbeshko, G.I.; Melnichuk, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
A possibility to use surface plasmon resonance (SPR) in the investigations of the microwave radiation influence upon proteins in the process of their adsorption on the gold surface and their interaction with other proteins. For the first time, this method is applied to experimental study of physical parameters of the biological molecules under the action of the weak (from 1 to 10 mW/ cm²) electromagnetic fields in real-time regime. The changes in the process of adsorption of protein on the gold at different stages of the absorption as well as the changes in the reaction of antigen-antibody were introduced under the action of microwave field. More dense layers of protein was obtained in the microwave fields resulting in the decreased contribution of non-specific and specific interactions between proteins.